The assessment of cholinesterase from the muscle of Anabas testudineus as detection of metal ions - Basirun, Ain Aqilah (2015)
Anabas testudineus, also known as Climbing Perch is a freshwater fish which originated from India and mostly inhabited in rivers and lakes. It came from family ‘Anabantidae’ and in Malaysia it is called ‘ikan puyu’. A. testudineus is a very hardy fish and is having high commerial value. Cholinesterase (ChE) was purified from the muscle extracts of A. testudineus through ion-exchange chromatography (DEAE-cellulose). In this study, ChE was partially purified with a purification folding and recovery yield of 2.012 and 14.46% respectively. Native-PAGE analysis was done to show the degree of purity. Optimisation study of muscle ChE was carried out shows that for muscle ChE, the specific substrate is propionylthiocholine iodide (PTC) at 2.5 mM, with optimum temperature and pH of 30°C and pH 9.0 respectively using Tris-HCl buffer. Metal ions inhibition study has shown that mercury had inhibited at highest percentage of enzyme activity, at 93.4%. Half-maximal inhibitory concentration by mercury obtained in this study was at 0.9752 mg/L. Hence, the ion-exchange chromatography shows that it is one of the useful purification methods to purify ChE from muscle of A. testudineus and ChE purified from this can be a useful biosensor for metal ion pollution monitoring in aquatic system.